Pengaruh Implementasi Manajemen Pendidikan Terhadap Peningkatan Mutu Dan Kualitas Pendidikan Di Sdit Al-Ikhlas Cirejag - Rizkiyah, Sifa Ikhsaniandita; Hafizhah, Salwa; Fadilah, Rizki; Suhardi, Tedy; Permana, Hinggil (Nirta Learning Centre, 2024)
Abstract. This study looks at how SDIT Al-Ikhlas Cirejag's administration has been working to raise the bar for classroom instruction. Management strategy implementation primarily entails three stages: development, execution, and assessment. During the formulation stage, the principal and teaching staff work together to establish the school's vision and purpose, which centers on Islamic religious education. This will help to maximize the accomplishment of objectives. Establishing regulations, engaging teaching personnel, and providing learning-supporting facilities and infrastructure are all part of implementing a strategy. Training and the GUMELIS learning community are two of the initiatives that have been put in place to try to raise the bar on education quality and teacher competence. The purpose of conducting evaluations is to track progress toward goals, with an emphasis on raising standards in Islamic religious education and academic performance among students. Findings demonstrate that equitable distribution of educational quality, student motivation, learning outcomes, teaching quality, and the use of technology all benefit from wellmanaged educational programs at SDIT Al-Ikhlas Cirejag. Abstrak. Studi ini mengkaji bagaimana administrasi SDIT Al-Ikhlas Cirejag berupaya meningkatkan standar pembelajaran di kelas. Implementasi strategi manajemen terutama mencakup tiga tahap: pengembangan, pelaksanaan, dan penilaian. Selama tahap perumusan, kepala sekolah dan staf pengajar bekerja sama untuk menetapkan visi dan tujuan sekolah, yang berpusat pada pendidikan agama Islam. Ini akan membantu memaksimalkan pencapaian tujuan. Menetapkan peraturan, melibatkan tenaga pengajar, dan menyediakan sarana dan prasarana pendukung pembelajaran merupakan bagian dari implementasi strategi. Pelatihan dan komunitas pembelajaran GUMELIS merupakan dua inisiatif yang telah dilakukan untuk mencoba meningkatkan standar kualitas pendidikan dan kompetensi guru. Tujuan dari pelaksanaan evaluasi adalah untuk melacak kemajuan menuju tujuan, dengan penekanan pada peningkatan standar dalam pendidikan agama Islam dan kinerja akademik di kalangan siswa. Temuan menunjukkan bahwa distribusi kualitas pendidikan, motivasi siswa, hasil belajar, kualitas pengajaran, dan penggunaan teknologi yang merata semuanya mendapat manfaat dari program pendidikan yang dikelola dengan baik di SDIT Al-Ikhlas Cirejag.